2012
DOI: 10.1158/1078-0432.ccr-12-2570
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Drug Monitoring of Imatinib—New Data Strengthen the Case

Abstract: A population pharmacokinetic study of imatinib in patients with gastrointestinal stromal tumor by Eechoute and colleagues has shown a significant increase in drug clearance over the first 3 months of treatment, resulting in a 30% decrease in drug exposure. This finding clearly shows the possibility of pharmacokinetic resistance in this disease.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Also, as mentioned previously, because of the decrease in systemic imatinib concentrations over time, target C min values after 1 month cannot be extrapolated into a dosing algorithm for the entire treatment period. Although it has been proposed that TDM be performed only after imatinib pharmacokinetics have stabilized after 3 months of treatment [ 11 ], whether or not an individual with GIST receives the proper treatment and dose would ideally become visible much earlier during treatment. For example, by using fludeoxyglucose (18F) [ 18 F-FDG] positron emission tomography [PET] as early as a few days after the start of treatment, it is possible to know whether or not a GIST patient is responding to treatment [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, as mentioned previously, because of the decrease in systemic imatinib concentrations over time, target C min values after 1 month cannot be extrapolated into a dosing algorithm for the entire treatment period. Although it has been proposed that TDM be performed only after imatinib pharmacokinetics have stabilized after 3 months of treatment [ 11 ], whether or not an individual with GIST receives the proper treatment and dose would ideally become visible much earlier during treatment. For example, by using fludeoxyglucose (18F) [ 18 F-FDG] positron emission tomography [PET] as early as a few days after the start of treatment, it is possible to know whether or not a GIST patient is responding to treatment [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, it has been shown that imatinib clearance increases—and systemic concentrations therefore decrease—during the first 3 months of treatment [ 9 , 10 ]. Hence, it could be expected upfront that an even larger proportion of patients than the 25 % in the phase II study would have a C min below 1100 ng/mL when it was determined later than 3 months after the start of treatment, and doubts have been raised as to whether this threshold set at a time when systemic exposure has not yet stabilized is indeed the appropriate target imatinib C min in patients with GIST [ 11 ]. Accordingly, in one of the more recent retrospective studies in GIST patients, a threshold of 760 ng/mL led to better prediction of the outcome [ 8 ].…”
Section: Introductionmentioning
confidence: 99%